Harassment in Universities through the Eyes of Students - N. A. Yastreb; K. A. Koryakina (Высшее образование в России)
The article is devoted to the study of the attitude of university students to the problem of harassment in universities, including the identification of their existing stereotypes. Within the framework of this research, domestic and foreign studies of harassment in the academic environment were analyzed and a questionnaire was developed to identify the ideas of university students about the essence and practices of harassment. In total, 250 full-time students from one of the Russian universities took part in the survey.The conducted research has shown that in the students’ view, harassment is not limited to sexual harassment and at the same time includes many practices that were previously fully or partially acceptable for the field of education. In the minds of students, there is a denormalization of bullying, evaluation and commenting on personality and appearance, discrimination based on gender, age, political views and other parameters. The most common stereotypes among students are that harassment is a media construct, that the older generation of men is the bearer of harassment practices, and only women become victims; there is also a widespread belief that the victim herself should cope with the situation in case of harassment. It was also recorded a polarization of opinions in the student environment about the reality of the problem and the essence of harassment and the strategies of action in case of harassment.As a result of the study by the authors of the article, proposals were formulated on the implementation of forms of preventing harassment and resolving conflict situations at the university level.